A case report on rare case of chronic osteomyelitis of the distal fibula in adult - Somani, Ashish; Shihora, Yashkumar B.; Herode, Prafulla (International Journal of Research in Orthopaedics, 2022)
Osteomyelitis of the fibula is uncommon. It can occur secondary to trauma however it can also occur as a result of haematogenous spread from distant sites of infection. There is usually a period of sub clinical infection and this can lead to delay in diagnosis. But it is clinical diagnosis with support of various investigation with proper surgical technique and various differential diagnosis it is treated with good satisfactory result. A 24-year-female was asymptomatic but for last 6 days She started developing pain, swelling and redness of skin from lateral aspect of distal third of leg. We investigated and did incision and pus drainage with abnormal tissue was excised out, but very unusual presentation intraoperative pus and tissue debris was there. However, after biopsy, it was diagnosed pyogenic osteomyelitis 2 weeks of injectable and 6 weeks of oral antibiotics were given. After 4-6 weeks weight bearing was started, the patient returned to his obvious activities with normal range of motion. The osteomyelitis of fibula with various differential diagnosis clinically and intraoperatively with pus discharge but after proper debridement and biopsy report probable diagnosis is made with proper duration of antibiotic treatment chronic osteomyelitis is treated with satisfactory result with good outcome.